Trends in Technology Literacy Research (2021 to 2025): A Bibliometric Analysis with VOSviewer - Frendi Ihwan Syamsudin; Ketang Wiyono; Evelina Astra Patriot; Ismet Ismet; Saparini Saparini; Azlan Kamari (Jurnal Materi dan Pembelajaran Fisika, 2025)
Technology literacy is a crucial competency in addressing digital transformation and the challenges of 21st-century learning. This study aims to analyze research trends in technology literacy within the field of education, particularly in STEM learning, through a bibliometric approach using VOSviewer. Data were collected from international publication databases for the period 2021–2025 using the keywords technology literacy, digital literacy, and STEM education. The analysis identified five main research clusters: (1) effects and impacts (effect, impact, relationship), (2) learning contexts and student engagement (student engagement, experience, perception), (3) digital adoption and mechanisms (adoption, tool, competency, mechanism), (4) sustainability and management (sustainability, management, industry), and (5) emerging technological innovations (virtual reality, healthcare, engineering, artificial intelligence). The findings indicate that technology literacy is not only associated with pedagogical practices and student learning in STEM but also extends to sustainability, industry, and advanced technologies. This broader scope highlights the novelty of this study, showing how technology literacy connects education with global technological advancements. The study provides valuable insights for academics and practitioners in developing adaptive and future-oriented learning strategies aligned with educational needs and technological change.